Novel L-tryptophan-functionalized zirconium dioxide nanoparticles catalysed one-pot and solvent-free synthesis of 2 H-indazolo [2, 1-b] phthalazine-triones - Ali Kareem Abbas; Javad Safaei-Ghomi; Samira Moein-Najafabadi (Scientific Reports)
Abstract Zirconia nanoparticles modified with L-tryptophan (ZrO₂@L-Try) demonstrate increased biocompatibility and catalytic activity by capitalizing on the bioactive properties of L-tryptophan, a crucial amino acid known for its role in protein synthesis and neurochemical functions. Successful integration of L-tryptophan onto the ZrO2 matrix is confirmed through characterization methods. This catalytic system was employed effectively in the synthesis of 2 H-indazolo[2,1-b]phthalazine-triones through multi-component, one-pot reactions involving phthalic anhydride, various aldehydes, dimedone, and hydrazinium hydroxide under thermal, solvent-free conditions at 80 °C. Investigations suggest that ZrO2@L-Tryptophan exhibits enhanced stability and solubility and holds promise as an innovative platform for drug delivery systems and an efficient catalyst in diverse organic reactions.